Political Marketing of Kusdinar Untung Yuni Sukowati- Dedy Endriyatno Campaign Team at Sragen Election 2015 - Faris Nuruddin, Muhammad; Yuliyanto, S.Sos, M.Si, Much. (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Kusdinar Untung Yuni Sukowati and Dedy Endriyatno are a candidates who managed to come out as the winner in the general election or election of regional heads Sragen 2015. The victory became an interesting study because they was able to defeat the incumbent with a considerable margin, was able to defeat candidateswho carried by the big party, the only pairs who are women candidates, and has a controversial political background. Therefore, this study aims to determine how the application of political marketing which carried campaign team of Kusdinar Untung Yuni Sukowati and Dedy Endriyatno in simultaneous election Sragen on December 9, 2015.This research is a qualitative descriptive study with case study approach. In this case the researchers are trying to collect data, information and finding meaning with the speaker on how to implement political marketing.The research subjects is Yuni-Dedy campaign team who know and undergo the process of political marketing during the campaign period. The results showed that Yuni-Dedy campaign team able to maximize the application of the marketing mix (4Ps) into political marketing activity.On the aspect of products, the campaign team noticed how packed platform, track record, and the personal characteristics of the couple Yuni-Dedy.On the aspect of promotion, the campaign team to do some strategic communications activities, such as advertising, personal selling, public relations (PR), direct marketing, and sales promotion. The activities are then used as a series of activities in the campaign Yuni-Dedy, both campaigns at district, sub-district, and village. The campaign team is assisted by each party cadres and volunteers.On the aspect of price, there is no imposition of price when voters choose Yuni-Dedy, but there is a belief and a trust that was sacrificed by voters. On the other hand, the campaign team was able to optimize the image attached to the pair Yuni-Dedy as something that is offered to voters.On the aspect of place, the campaign team was able to distribute political messages to different places and do the mapping to analyze the competitive landscape of politics.